Trust in Tax Authorities, Tax Fairness and Tax Morale: A Conceptual Review - Teh Suhaila Tajuddin; Izlawanie Muhammad; Mohd Adha Ibrahim (Fakulti Ekonomi dan Muamalat, Universiti Sains Islam Malaysia, 2024)
10th INTERNATIONAL ISLAMIC ECONOMIC SYSTEM CONFERENCE 2023 (I-iECONS 2023) : “Sustainable Development through Innovative Economic Transformation” /Editors : Amalina Mursidi, Agoos Munalis Tahir, Suhaida Herni Suffarruddin, Norfhadzilawati Rahim, Murad Ali Ahmad Al-Zaqeba, Muhammad Iqmal Hisham Kamaruddin Conference Dates: August 14 2023 | Conference Location: Millennium Makkah Al Naseem Hotel Mecca Saudi Arabia Organized by Faculty of Economics and Muamalat